-5(2b+3)+(11b-7)=0

Simple and best practice solution for -5(2b+3)+(11b-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2b+3)+(11b-7)=0 equation:


Simplifying
-5(2b + 3) + (11b + -7) = 0

Reorder the terms:
-5(3 + 2b) + (11b + -7) = 0
(3 * -5 + 2b * -5) + (11b + -7) = 0
(-15 + -10b) + (11b + -7) = 0

Reorder the terms:
-15 + -10b + (-7 + 11b) = 0

Remove parenthesis around (-7 + 11b)
-15 + -10b + -7 + 11b = 0

Reorder the terms:
-15 + -7 + -10b + 11b = 0

Combine like terms: -15 + -7 = -22
-22 + -10b + 11b = 0

Combine like terms: -10b + 11b = 1b
-22 + 1b = 0

Solving
-22 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 1b = 0 + 22

Combine like terms: -22 + 22 = 0
0 + 1b = 0 + 22
1b = 0 + 22

Combine like terms: 0 + 22 = 22
1b = 22

Divide each side by '1'.
b = 22

Simplifying
b = 22

See similar equations:

| 5w-10=2w+17 | | -2+7a=-5a+130 | | -6x+8=-x+8 | | -4n+7=70+3n | | -10+3t=-6t-28 | | 3x+4=16+2x | | 5m-1=2m+8 | | 1+7b=-6b+157 | | 3a-9=-24+6a | | 10+2x=-5x+31 | | 4b+3=-3b+17 | | -2x-2=-6x-18 | | -7k+7=-4k+19 | | -6-4w=4w-14 | | 4.6q-5.4-5.7q=2.1q-2.1 | | 5d+8=-d+26 | | -7+3d=-6d+83 | | -3t+4=32+t | | w+1=26+6w | | -7a-5=-3a-17 | | 2-3x=5x-30 | | 3+6d=-6d+135 | | -8*8/35=b | | -5+3w=6w+16 | | 4+t=3t-18 | | -2w+7=2w-29 | | n+2=-46-5n | | 7/8*5=b | | -6m-10=-19+3m | | 4x+8=4+3x | | 6t+8=18+7t | | 10-2x=x-26 |

Equations solver categories